The End User Requirement for Project Management Software Accuracy - Fachrurrazi Fachrurrazi (Institute of Advanced Engineering and Science, 2018)
This research explains the relationship between the end user requirement and accuracy of PMS (Project Management Software). The research aims are to analyze the PMS accuracy and measuring the probability of PMS accuracy in achieving ±1% of the end user requirement. The bias statistical method will be used to prove the PMS accuracy that based on the hypothesis testing. The result indicates the PMS is still accurate to be implemented in Aceh-Indonesia area projects that using the SNI (National Indonesia Standard as current method) with the accuracy index of ±7.5%. The achievement probability of reaching the end user requirement is still low of ±21.77%. In case of the PMS, the low achievement of the end user requirement is not only caused by the low accuracy of the PMS but also caused by the amount of variability error, which is influenced by the amount of variation of the project activity. In this study, we confirm that it is necessary to reconcile both conditions between the PMS accuracy and the end user requirements.